2022
DOI: 10.1161/circulationaha.121.055459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Glucagon-Like Peptide-1 Receptor Agonists Semaglutide and Liraglutide on Kidney Outcomes in Patients With Type 2 Diabetes: Pooled Analysis of SUSTAIN 6 and LEADER

Abstract: Background: We assessed the effect of once-weekly semaglutide and once-daily liraglutide on kidney outcomes in type 2 diabetes (T2D). Methods: Pooled (N=12,637) and by-trial data from SUSTAIN 6 (N=3297) and LEADER (N=9340) were assessed for albuminuria change, annual slope of estimated glomerular filtration rate (eGFR) change, and time to persistent eGFR reduction (30%, 40%, 50%, and 57%) from baseline. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 32 publications
5
107
0
3
Order By: Relevance
“…Notably, treatment-induced improvement in the eGFR slope was greater in the subgroup of patients with eGFR < 60 mL/min/1.73 m 2 than in those with preserved kidney function at baseline. Compared with placebo, therapy with semaglutide or liraglutide provoked a 14% (HR: 0.86; 95% CI: 0.75-0.99) and 20% (HR: 0.80; 95% CI: 0.66-0.97) reduction in the risk for sustained 40% and 50% declines in eGFR during follow-up, respectively [43]. Similarly, directional but not statistically significant reductions were evident for the risk of sustained 30% and 57% decline in eGFR.…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 97%
See 2 more Smart Citations
“…Notably, treatment-induced improvement in the eGFR slope was greater in the subgroup of patients with eGFR < 60 mL/min/1.73 m 2 than in those with preserved kidney function at baseline. Compared with placebo, therapy with semaglutide or liraglutide provoked a 14% (HR: 0.86; 95% CI: 0.75-0.99) and 20% (HR: 0.80; 95% CI: 0.66-0.97) reduction in the risk for sustained 40% and 50% declines in eGFR during follow-up, respectively [43]. Similarly, directional but not statistically significant reductions were evident for the risk of sustained 30% and 57% decline in eGFR.…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 97%
“…Similarly, directional but not statistically significant reductions were evident for the risk of sustained 30% and 57% decline in eGFR. Once again, when the analysis was restricted to patients with eGFR of 30-60 mL/min/1.73 m 2 at baseline, the renoprotective benefit of GLP-1 receptor agonists was greater in magnitude (HR: 0.71, 0.67, 0.56, and 0.54 for sustained 30%, 40%, 50%, and 57% decline in eGFR, respectively) [43]. Taken together, this exploratory analysis of LEADER and SUSTAIN-6 trials suggests that the renoprotection afforded by GLP-1 receptor agonists is likely more pronounced in patients with T2DM and pre-existing CKD than in those with preserved kidney function.…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 98%
See 1 more Smart Citation
“…The half-life of natural GLP-1 is very short (1–2 min) because it is rapidly degraded by the ubiquitous proteolytic enzyme DPP-4 ( Bell et al, 1983 ; Hansen et al, 1999 ). Recently, dipeptidyl peptidase-4 inhibitor (DDP-4i) and GLP-1 receptor agonists (GLP1RA) have been widely used in anti-hyperglycemic medications by interfering with GLP-1 expression ( McGuire et al, 2019 ; Shaman et al, 2022 ). Recent studies demonstrated that DDP-4i and GLP-1RA could not only control blood sugar by regulating the secretion of insulin, but also exert anti-inflammatory and reno-protective effects in DKD ( Gangadharan et al, 2016 ; Coppolino et al, 2018 ; Shaman et al, 2022 ).…”
Section: Anti-inflammation Treatment In Dkdmentioning
confidence: 99%
“…Contrary to the above-mentioned trials, both in the LEADER trial [ 16 ] and the SUSTAIN-6 trial [ 20 ], evaluating Liraglutide and Semaglutide, respectively, there were no prespecified renal outcomes. In a recent pooled analysis of these trials, a decrease in albuminuria and eGFR decline was noted [ 35 ]. These effects were pronounced in patients with preexisting renal failure.…”
Section: Glucagon-like Peptide-1 Receptor Agonists (Glp-1ra)mentioning
confidence: 99%